Practice and pricing in non-life insurance: the Malaysian experience - Pan, Wei Cheong; Abdul Aziz Jemain,; Noriszura Ismail, (Penerbit ukm, 2008)
The pricing of premium for fire, motor and workmen’s compensation insurances in Malaysia is governed by their respective tariffs formulated by Persatuan Insurans Am Malaysia (PIAM). The main objective of tariffs is to guarantee that the premium price will always be above or at the level required, ensuring that the price competition among local insurers will not go below the market’s economic level. However, one of the effects caused by the world economic crisis in 1997 is the process of liberalization which spread gradually in most financial sectors in Malaysia, including non-life insurance sector. Therefore, a thorough and comprehensive preparation towards the development of a more matured and open insurance market is one of the challenges that should be undertaken by the sector and regulatory concerned. One of the important tasks that should be given serious attention is the determination of “appropriate” premium price in low premium and high volume insurance businesses. This paper proposes a statistical modelling for determining the price of such insurance businesses. The result of statistical premium pricing is presented in a premium table